micro-Raman and micro-Photoluminescence study of ZnO thin films - Urbina-Yarupetan, M. A. (2021)
We present the experimental results of optical analysis of nanostructured ZnO thin films grown onto commercial glass by reactive sputtering. Films with 20, 50, and 100 nm in thickness were analyzed by micro-Raman and micro-photoluminescence spectroscopies. Raman and photoluminescence bands were deconvoluted with Lorentzian profiles, in order to obtain information about response of films to excitation with laser light, occurring changes in position, full width half maximum (FWHM), and area of each phonon and emission bands of ZnO, correlating them with its nanostructure nature, and packing morphology of ZnO nanocolumns.